On the thermophoretic sampling and TEM-based characterisation of soot particles in flames. (January 2021) - Botero, Maria L.; Akroyd, Jethro; Chen, Dongping; Kraft, Markus; Agudelo, John R.
Abstract: Thermophoretic sampling and TEM imaging are common techniques used to characterise soot particles in flames. In this paper, we present a multi-scale evaluation of operating conditions and methodological aspects of these techniques, and based on our own experimental observations, show how these can influence the characterisation of the particles. Regarding the thermophoretic sampling of soot particles in flames, we evaluated the influence of exposure time, transit times, multiple-insertions, probe design and vibrations in the capture of representative samples, and present a series of recommendations. For the nano-structural characterisation of soot particles using HRTEM combined with fringe analysis we evaluated the influence of microscope alignment and image quality in the mapping of fringes and the calculation of metrics, concluding that the fringe lengths and inter-fringe spacing are very sensitive to particle focus. Also, the parameters used in the image transformation process are critical and require optimisation for different magnifications and microscopes. Finally, the effect of beam damage was studied, confirming a time of approximately 6 min during which both nascent and mature particles can be imaged without noticeable nano-structural damage. The use of lower microscope electron voltage can further minimise the impact of beam damage. Graphical abstract: Image 1